2009
DOI: 10.1007/s10404-009-0409-6
|View full text |Cite
|
Sign up to set email alerts
|

Advanced particle-based velocimetry techniques for microscale flows

Abstract: Recently, microscale flows have been receiving large attention in various research areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 73 publications
0
34
0
1
Order By: Relevance
“…Fluorescent nano/micro beads are typically used as tracers, and a confocal microscope can be used to deduce the velocity distribution in three dimensions [51][52][53][54][55][56][57][58][59]. Evanescent waves generated by total index reflection of a laser can be used to derive the velocity near the liquid/wall interface, within approximately 50 nm, when they are used as the excitation light for the fluorescent tracer particles [60][61][62][63][64].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent nano/micro beads are typically used as tracers, and a confocal microscope can be used to deduce the velocity distribution in three dimensions [51][52][53][54][55][56][57][58][59]. Evanescent waves generated by total index reflection of a laser can be used to derive the velocity near the liquid/wall interface, within approximately 50 nm, when they are used as the excitation light for the fluorescent tracer particles [60][61][62][63][64].…”
Section: Introductionmentioning
confidence: 99%
“…It also has good linearity over most of its range, which is much larger than that available with QPD detection. Other 3D tracking methods have used the point spread function [15,16], contrast inversion [17] or digital holography [18]. These techniques obtain good resolution, at the expense of relatively demanding image analysis.…”
Section: D Position Measurementmentioning
confidence: 99%
“…The axial position can therefore be found by tracking an object in 2D in each image and measuring the apparent difference in position. Commercial stereomicroscopes are designed with small angles (around 10 • ) between viewpoints, and as such achieve relatively coarse axial resolution [15]. It is also possible to use two separate microscope objectives [7], however this results in a large optical system and requires special sample cells.…”
Section: D Position Measurementmentioning
confidence: 99%
“…During the last 10 years, the μPIV technique has been used in many research fields, for example, to study electroosmotic, pressure driven and mixed flow in a twin-T microchannel intersection [34], thermal measurement dependent Brownian motion of microparticles [35], investigation of fluid slip mechanisms at wall [36] and in hydrophobic microchannels, internal circulation of aqueous plugs in two phases flow [37], in measurements of beads suspensions in water and human blood, using the red blood cells as a natural particle seeding [38]. A comprehensive review on the μPIV technique can be found in [39] and [40].…”
Section: Micro-particle Image Velocimetrymentioning
confidence: 99%